Exploring Novel Y140F/H Mutant Fungal CYP51 Inhibitors: A Molecular Docking and Dynamics Study on Thiophene Compounds - Abdulrahim A. Alzain; Alaa Edris; Rua M. Mukhtar; Hagar M. Mohamed; Malek Abdullah Marzoqi Aldowimar; Ali A. Alqarni; Gamal A. Mohamed; Sabrin R. M. Ibrahim (Journal of Pharmacy and Bioallied Sciences)
Background: Invasive fungal infections (IFIs) pose a significant risk specifically to the health of immunocompromised individuals, leading to a substantial number of deaths annually. Therapeutic options for IFIs are limited compared to bacterial infections, with only three classes of antifungal medications currently in use. The widespread use of triazole antifungals for IFI prevention and treatment, along with long treatment durations, has led to the emergence of severe drug resistance, indicating the urgent need for intervention to address this critical issue. This study aims to identify novel inhibitors for the Y140F/H fungal CYP51 enzyme. Methods: Molecular docking and molecular dynamics were utilized to evaluate 161 thiophene compounds for their inhibitory potential against the mutant CYP51. Findings: The docking process involved two stages: docking on the wild type followed by docking on the mutant type, leading to the discovery of three compounds (referred to as compounds 1, 2, and 3) with better docking scores than the reference, indicating stronger binding affinity. Subsequent molecular dynamics simulations demonstrated that these three compounds displayed favorable stability and flexibility characteristics. Conclusion: Based on our findings, we suggest that compounds 1, 2, and 3 have the potential to act as inhibitors of the Y140F/H CYP51 enzyme.